Thoughts on the criminal prisons of this country, occasioned by the bill now in the House of Commons, for consolidating and amending the laws relating to prisons . with some remarks [...].; (Rivington etc., 1821)
(Repr.: Pamphleteer. 1821, vol. XVIII, no 35, p. 145-190).